The Application of Creative Problem Solving (CPS) Models with Puppet Media (Cartoons) To Increase Student Understanding Activities - Veronika Agustin (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
The purpose of the research is to know how to apply Creative Problem Solving model with Wayang Media (Cartoon) to the understanding of student. The type of research used is classroom action research with Hopkins model research design that begins with preliminary action then proceeded by planning, action, observation, and reflection. Based on research result the application of Creative Problem Solving model with Wayang Media (Cartoon) can improve understanding and students activity. This is evident from the percentage of student learning activities on learning cycle I for 77.7% with good enough category and cycle II of 86.8% with good category. This shows an increase of 9.1%. Completeness of student learning outcomes on prerequisite materials obtained from pre-cycle pretest is 80.8%. While the completeness of student learning outcomes in learning cycle I reached 84.6% with good category and has reached the percentage of completeness in a classical. While in the second cycle reached 96.2% with very good category. Keywords: creative problem solving, wayang media